TRANSFORMASI KOMUNIKASI ORGANISASI MELALUI TEKNOLOGI DIGITAL: STUDI LITERATUR TERBARU - Nyi Dewi Puspitasari; Aslan Aslan (ADISAM PUBLISHER, 2025)
The transformation of organisational communication driven by the adoption of digital technologies is bringing about major changes in the way employees interact, collaborate and work. Digital technologies such as email, video conferencing, and collaboration platforms enable greater efficiency, rapid response to change, and opportunities for innovation. Data analytics enable decision-making that is better informed by accurate information, improve communication strategies, and increase employee engagement and satisfaction. However, the adoption of digital technologies in organisational communications also presents challenges. Information overload can lead to information overload, lowering productivity and reducing the quality of communication between individuals. In addition, cybersecurity risks are increasing, requiring special attention to data and information protection. The shift to digital communication also has the potential to reduce face-to-face interactions, which can change the dynamics of interpersonal relationships in the workplace. To take full advantage of the positive impact of this transformation, organisations should develop comprehensive management strategies, provide ongoing training, and enhance digital security measures